1995
DOI: 10.1063/1.871247
|View full text |Cite
|
Sign up to set email alerts
|

Effect of toroidal plasma flow and flow shear on global magnetohydrodynamic MHD modes

Abstract: The effect of a subsonic toroidal flow on the linear magnetohydrodynamic stability of a tokamak plasma surrounded by an external resistive wall is studied. A complex non-self-adjoint eigenvalue problem for the stability of general kink and tearing modes is formulated, solved numerically, and applied to high β tokamaks. Results indicate that toroidal plasma flow, in conjunction with dissipation in the plasma, can open a window of stability for the position of the external wall. In this window, stable plasma bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
239
1
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(250 citation statements)
references
References 12 publications
9
239
1
1
Order By: Relevance
“…In contrast to previous studies [3,4], this complete stabilization is obtained without adding parallel damping to the ideal magnetohydrodynamic (MHD) model. Our approach couples the plasma, which has an equilibrium flow, to the resistive wall by using a Green's function, so that the vacuum region is not discretized.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…In contrast to previous studies [3,4], this complete stabilization is obtained without adding parallel damping to the ideal magnetohydrodynamic (MHD) model. Our approach couples the plasma, which has an equilibrium flow, to the resistive wall by using a Green's function, so that the vacuum region is not discretized.…”
mentioning
confidence: 90%
“…A proven method to stabilize the RWM is for the plasma to have equilibrium flow [1]. This method has also been explored theoretically [2] and numerically [3,4].…”
mentioning
confidence: 99%
“…These discharges are calculated to be unstable to a resistive interchange and are also unstable to a double tearing mode in the absence of plasma rotation. The strong rotational shear stabilizes the double tearing, but bursts of MHD, localized in the negative shear region and possibly a resistive interchange reduces the rotational shear and may drive the double tearing unstable (Chu 1995(Chu , 1996Strait 1997).…”
Section: Ts Taylormentioning
confidence: 99%
“…In these experiments, there is a rapid toroidal rotation due to unbalanced neutral beam injection. Theoretically, it is shown that the combination of plasma rotation and some dissipation model can stabilize RWMs [4][5][6][7]. When the RWMs are destabilized, the RWM results in major collapse.…”
Section: Introductionmentioning
confidence: 99%